Investigation of quality indicators and studying the stability of "Propolis-AK" gel for the treatment of acne disease - А. I. Tykhonov; T. G. Yarnykh; S. G. Bobro; O. S. Shpychak (The State Expert Center of the Ministry of Health of Ukraine, 2019)
In modern conditions, the incidence of acne, which is a polymorphic multifactorial disease of the sebaceous glands of the skin, has a tendency to significant growth. Localization of lesions on the face in almost all patients indicates the fact that acne has an effect on their psycho-emotional sphere and social adaptation, which makes this problem urgent and indicates the feasibility of creating new effective domestic medicines for treating this pathology. The aim of the work was to conduct research on the investigation of quality indicators and studying the stability of «Propolis-AK» gel of anti-inflammatory and antimicrobial action for the treatment of acne disease. The objects of research were model test-samples of «Propolis-AK» gel, for which were developed methodic for analyzing the qualitative composition and quantitative content of the active substances - propolis phenolic hydrophobic drug (PPHD) and azelaic acid (AA) in this dosage form, comprehensively allowing to evaluate the quality and criteria for the stability of the gel during the entire storage period for the following indicators: description, identification, homogeneity, tightness of the container, pH, package contents, microbiological purity, quantification. In addition, the requirements for packaging, labeling, transportation, storage conditions and shelf life were included in the draft of quality control methods. According to the results of the study of organoleptic and physical-chemical parameters of the developed «Propolis-AK» gel during storage at two temperature conditions (8‒15 °C and 15‒25 °C), it was found that the test samples of the gel under study remained fairly stable according to the studied indicators for 2 years and 3 months, which allows us to recommend a shelf life of 2 years at room temperature in aluminum tubes for the studied gel. According to the results of research, a specification for «Propolis-AK» gel for external use was developed as a component of the draft of quality control methods for the studied medicine. Studies have been conducted to establish the main indicators and methods of quality control of the developed «Propolis-AK» gel for the treatment of acne disease. According to the results of the tests, a "Specification" was developed, which was included in the draft of quality control methods and experimentally proved the stability of «Propolis-AK» gel prepared in pharmaceutical and industrial conditions for a prescribed shelf life of 24 months when stored in aluminum tubes with an internal lacquer coating in a cool place (8‒15 °C) and at room temperature (15‒25 °C).